The Quest of the Volk(swagen): The Bricklin Car, Industrial Modernity, and New Brunswick - Anastakis, Dimitry (Acadiensis, 2014)
Three thousand Bricklin cars were built in New Brunswick between 1974 and 1976 with government support before the company went bankrupt.  This article examines the Bricklin as an idea of industrial modernity, reflecting a long-standing thread within national policies around the world linking the emergence of a successful automotive sector to economic and political maturity.  It shows how politicians, policymakers, and the media attempted, through Bricklin, to shape collective and regional identity in order to achieve an industrial modernity that was associated with car manufacture.  Bricklin was far more than a simple car company – it was an attempt to reshape the very idea of a province.